Technological ageing influence on viscosity of selected bitumens - Radziszewski, Piotr; Ziolkowski, Robert; Čygas, Donatas (Journal of Civil Engineering and Management, 2003)
The article presents one of the main parameters of bitumens used for asphalt concrete mixtures production – viscosity. The authors analyse technological ageing process and its influence on viscosity of selected bitumens. Dependence of the viscosity of bitumens on type and amount of the additives, temperature and ageing is described through experiments. Research findings show that the employment of different types of additives increases bitumen viscosity and positively effect the bitumen ageing resistance. Practical application of presented conclusions and recommendations will enable to improve the main characteristics of asphalt concrete pavements and traffic conditions on roads.First Published Online: 26 Jul 2012